6 Evaluating the Impacts of Starvation on Permethrin Resistant and Susceptible Horn Flies (Diptera: Muscidae). (22nd October 2022) - Ramirez, Jovannah; Sanchez-Sandoval, Ulises A; Figueroa-Zamudio, Joaquin J; Walker, Hannah L; Smythe, Brandon G
Abstract: The objective of the current study is to evaluate the impact of induced starvation on horn fly susceptibility to permethrin and general reproduction using filter paper and manure bioassays, respectively. Incorporating push-pull systems for horn fly control has recently gained much attention for use in managing this pest. However, the consequences of temporary starvation associated with the relocation of horn flies from one host to another have yet to be fully explored. Susceptible (SS) and permethrin resistant (PR) horn flies were randomly allocated to one of four treatment groups: 1- blood fed, 2- partially starved (4hr), 3- moderately starved (8hr), and 4- severely starved (12hr). Permethrin resistant flies were 1, 227 times more (P < 0.05) tolerant to permethrin in comparison to SS flies. Furthermore, SS blood fed flies were 1.18, 1.89, and 3.12 times more tolerant to permethrin than SS flies starved for 4, 8, and 12 hours, respectively. Egg hatching rates decreased (P < 0.04) for 8hr and 12hr starved flies in comparison to blood fed flies. Larval development, as measured through manure bioassays was lower (P = 0.02) in severely starved flies in comparison to blood fed flies. Pupae sizes were unaffected (P = 0.58) by starvation and fly strain. These results indicate that susceptibility to permethrin increases as time without a blood meal increases and furthermore, offspring success is reduced specifically through egg viability. Findings from this work will help further expand current integrated pest management options for animal producers by increasing our understanding and implementation of push-pull strategies in animal production systems.